2016
DOI: 10.1002/2015ef000348
|View full text |Cite
|
Sign up to set email alerts
|

The response of runoff and sediment loading in the Apalachicola River, Florida to climate and land use land cover change

Abstract: The response of runoff and sediment loading in the Apalachicola River under projected climate change scenarios and land use land cover (LULC) change is evaluated. A hydrologic model using the Soil and Water Assessment Tool was developed for the Apalachicola region to simulate daily runoff and sediment load under present (circa 2000) and future conditions (2100) to understand how parameters respond over a seasonal time frame to changes in climate, LULC, and coupled climate/LULC. The Long Ashton Research Station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…Recent studies have found that climate change affects local rainfall amounts, surface runoff, and distribution of water resources (Guo et al 2002;Akhtar et al 2008;Arnell and Gosling 2013;Kling et al 2014). Climate change is characterized by shifts in temperature and precipitation, with regionally specific responses, e.g., alteration of extremes, intensities, frequencies, and spatial and temporal patterns (Easterling et al 2000;Hay et al 2011;Wang et al 2013;Hovenga et al 2016). Hovenga et al (2016) addressed the effects of climate change on overland processes, river inflow, and sediment loading for the Apalachicola River region in Florida, USA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that climate change affects local rainfall amounts, surface runoff, and distribution of water resources (Guo et al 2002;Akhtar et al 2008;Arnell and Gosling 2013;Kling et al 2014). Climate change is characterized by shifts in temperature and precipitation, with regionally specific responses, e.g., alteration of extremes, intensities, frequencies, and spatial and temporal patterns (Easterling et al 2000;Hay et al 2011;Wang et al 2013;Hovenga et al 2016). Hovenga et al (2016) addressed the effects of climate change on overland processes, river inflow, and sediment loading for the Apalachicola River region in Florida, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is characterized by shifts in temperature and precipitation, with regionally specific responses, e.g., alteration of extremes, intensities, frequencies, and spatial and temporal patterns (Easterling et al 2000;Hay et al 2011;Wang et al 2013;Hovenga et al 2016). Hovenga et al (2016) addressed the effects of climate change on overland processes, river inflow, and sediment loading for the Apalachicola River region in Florida, USA. Within the wet seasons, the A1B scenario had the largest loadings and A2 was typically largest during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…alteration of extremes, intensities, frequencies, spatial and temporal patterns (Easterling et al, 2000;Hay et al, 2011;Hovenga et al, 2016;Wang et al, 2013). Hovenga et al, (2016) addressed the effects of climate change on overland processes, river inflow, and sediment loading for the Apalachicola region. Within the wet seasons, the A1B scenario had the largest loadings and A2 was typically largest during the dry season.…”
Section: Introductionsmentioning
confidence: 99%
“…In keeping with IPCC carbon emission scenarios, projected 2100 A2, A1B, and B1 LULC provided by the United States Geological Survey Earth Resources Observation and Science (USGS EROS) Center were selected to assess LULC change impacts (USGS EROS Center 2014). Detailed procedures for model calibration and validation, as well as climate change and LULC projections, are described in Hovenga et al (2016). The coupling of both future climate and LULC change was simulated for each GCM.…”
Section: Hydrologic Modelingmentioning
confidence: 99%